2015
DOI: 10.1080/20548923.2015.1133119
|View full text |Cite
|
Sign up to set email alerts
|

The ceramic ecology of florida: compositional baselines for pottery provenance studies

Abstract: The success of pottery provenance studies is fundamentally dependent upon spatially patterned variation in the composition of exploited clay resources. Uniformity in clay composition within a region and recognizable differences between regions of interest are essential requirements for determining provenance, but these parameters are difficult to satisfy in study areas such as the coastal plain of the southeastern USA in which chemical and mineralogical variation tend toward continuous gradients. In an attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Each pottery sample derives from a unique earthenware vessel, represented by one or more sherds or nearly complete containers. The pottery data were compared to NAA results of 130 clay samples from throughout the region (Wallis, Gilmore, et al 2015).…”
Section: Sampling and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each pottery sample derives from a unique earthenware vessel, represented by one or more sherds or nearly complete containers. The pottery data were compared to NAA results of 130 clay samples from throughout the region (Wallis, Gilmore, et al 2015).…”
Section: Sampling and Methodsmentioning
confidence: 99%
“…Patterned variation in the bulk chemistry of clays is discussed in detail elsewhere and only briefly summarized here (see Wallis, Gilmore, et al 2015). Based on NAA results, a maximum of 14 compositional regions can be identified, mostly between 100 km and 300 km in extent.…”
Section: Claysmentioning
confidence: 98%
See 1 more Smart Citation
“…In Florida, we have found that clays exhibit broad geographic patterns in mineral inclusions and bulk chemistry that are useful markers for pottery provenance studies (Wallis et al 2015). More than a dozen elements measured by NAA and mineral inclusions such as muscovite, calcareous matrix, phosphatic nodules, and siliceous microfossils observed in petrographic thin section show patterned distributions.…”
Section: Comparative Clay Samples In Archaeological Research: Potentimentioning
confidence: 99%
“…Our vessel lot table also includes summary data for NAA and petrographic analysis. Specifically, we have employed the groupings for these variables developed by Wallis and colleagues (Wallis et al 2015). At this time, we have retrieved NAA data for 512 sherds (representing an equal number of vessel lots) from our study area.…”
Section: Description Of the Databasementioning
confidence: 99%